Defensa de trabajos de titulación - Llivi Ruilova, Danny Vicente (2024)
The Dr. Gabriel Galarza López campus was the conducive setting for the defense of the degree works of the Engineering in Disaster Administration and Risk Management career, of the Faculty of Health and Human Sciences of the UEB.